Method for the control verification of digital information, represented in a residue number system - Krasnobayev, Victor; Yanko, Alina; Tur, Serhii (Національний технічний університет "Харківський політехнічний інститут", 2020)
The subject of the research in the article is the control methods for the data presented in the residue number system. The object of research is the process of monitoring data presented in the residue number system. The purpose of the work is to develop a method for increasing the reliability of control of data presented in the residue number system. The following tasksare solved in the article: research of data control methods presented in the residue number system; development of a method for increasing the reliability of data control; consideration of examples ofapplication of the developed method for a specific residue number system; demonstration of examples of calculation and comparative analysis of the reliability of data control presented in the residue number system. The following research methods are used: the basics of system analysis and the basics of machine arithmetic in the residue number system. The following results were obtained: A method for increasing the reliability of data control was developed; examples of application of the developed method for a specific residue number system are presented; examples of calculation and comparative analysis of the reliability of data control presented in the residue number system are given. Conclusions: This article presents the theoretical foundations of the process of increasing the reliability of control of data presented in the residue number system, based on the use of the procedure of zeroing numbers. A method for increasing the reliability of data control has been directly developed and presented. Examples of application of the developed method for a specific residue number system are given and examples of calculating the reliability of control of data presented in the residue number system are given. A method has been developed to increase the reliability of data control; it is a definite contribution to the theory of noise-resistant coding in a residue number system. Examples of calculation and comparative analysis of the reliability of data control confirm the practical significance of the results of this article.

Предметом дослідження в статті є методи контролю даних, представлених в системі залишкових класів. Об'єкт досліджень - процес контролю даних, представлених в системі залишкових класів. Мета роботи - розробка методу підвищення достовірності контролю даних, представлених в системі залишкових класів. У статті вирішуються наступні завдання: дослідження методів контролю даних, представлених в системі залишкових класів; розробка методу підвищення достовірності контролю даних; розгляд прикладів застосування розробленого методу для конкретної системи залишкових класів; демонстрація прикладів розрахунку і порівняльного аналізу достовірності контролю даних, представлених в системі залишкових класів. Використовуються такі методи дослідження: основи системного аналізу та основи машинної арифметики в системі залишкових класів. Отримані наступні результати: Розроблено метод підвищення достовірності контролю даних; представлені приклади застосування розробленого методу для конкретної системи залишкових класів; наведені приклади розрахунку і порівняльного аналізу достовірності контролю даних, представлених в системі залишкових класів. Висновки: В даній статті представлені теоретичні основи процесу підвищення достовірності контролю даних, представлених в системі залишкових класів, на основі використання процедури нулевізації чисел. Безпосередньо розроблений і представлений метод підвищення достовірності контролю даних. Наведені приклади застосування розробленого методу для конкретної системи залишкових класів інаведені приклади розрахунку достовірності контролю даних, представлених в системі залишкових класів. Розроблено метод підвищення достовірності контролю даних, є певним внеском в теорію завадостійкого кодування в системі залишкових класів. Приклади розрахунку і порівняльного аналізу достовірності контролю даних підтверджують практичну значимість результатів даної статті.
Метод контрольної перевірки цифрової інформації, представленої в системі залишкових класів
Keywords: control system of information; data transmission and processing system; nulevization of number; residue number system; обнуління числа; система передачі та обробки даних; система у правління інформацією; система числення